Relationship Between Mother's Education Level and Toddler Growth - Huda Rohmawati; Weni Tri Purnani (Universitas STRADA Indonesia, 2022)
Growth is a change in number due to the addition of cells and the formation of new proteins thereby increasing the number and size of cells in all parts of the body. The purpose of this study was to determine the relationship between education level and toddler growth in the working area of the Sukorame Community Health Center, Kediri.This research used a cross-sectional approach with a purposive sampling technique. The population is taken from all mothers who have toddlers in July. In accordance with predetermined research criteria, 68 mothers with toddlers were obtained as samples. The results of the Spearman correlation test obtained a significant value (p) value = 0.001 so that p <α, which means H0 is rejected and H1 is accepted, meaning that there is a relationship between education level and toddler growth in the working area of the Sukorame Health Center. It is expected that health workers can provide health education, especially mothers who have toddlers, about monitoring and early detection of growth deviations in toddlers. So that the incidence of mortality and morbidity can be reduced or suppressed.